Anthropometric measures at age 3 years in associations with prenatal and postnatal exposures to chlorophenols. (August 2019) - Guo, Jianqiu; Wu, Chunhua; Zhang, Jiming; Jiang, Shuai; Lv, Shenliang; Lu, Dasheng; Qi, Xiaojuan; Feng, Chao; Liang, Weijiu; Chang, Xiuli; Zhang, Yubin; Xu, Hao; et al.
Abstract: Background: Chlorophenols (CPs), suspected as endocrine disrupting chemicals, exposure during early life may contribute to body size. However, limited human data with inconsistent findings have examined the developmental effects of CPs exposure. Objective: To explore associations between prenatal and postnatal CPs exposure and anthropometric parameters in children aged 3 years. Methods: A subset of 377 mother-child pairs with urinary five CP concentrations were enrolled from a prospective birth cohort. Generalized linear models were conducted to evaluate associations of CPs exposure with children's anthropometric measures. Results: Maternal urinary 2, 4, 6-trichlorophenol (2, 4, 6-TCP) concentrations were significantly negatively associated with weight z scores [regression coefficient (β) = −0.51, 95% confidence interval (CI): -0.96,  −0.05; p  = 0.01], weight for height z scores (β = −0.54, 95% CI: -1.02,  −0.06; p  = 0.01) and body mass index (BMI) z scores (β = −0.53, 95% CI: -1.03,  −0.03; p  = 0.01) of children aged 3 years, after adjustment for potential confounders and postnatal CPs exposure. In the sex-stratified analyses, these inverse associations remained among boys, while in girls, positive associations of prenatal 2, 4, 6-TCP exposure with weight for height z scores and BMI z scores were observed. Postnatal exposure to 2, 5-diclorophenol (2, 5-DCP) was positively associated with weight z scores (β = 0.26, 95% CI: 0.02, 0.50; p  = 0.04), after controlling for possible confounders and maternal CPs exposure during pregnancy. Considering potential sex-specific effects, these associations were only observed in girls. Conclusions: Our findings indicate that prenatal 2, 4, 6-TCP exposure and postnatal 2, 5-DCP exposure may have adverse and sex-specific effects on children's physical development. Highlights: Chlorophenols (CPs) were prevalent in the studied pregnant women and children. Higher prenatal 2, 4, 6-TCP exposure predicted decreases in physical growth of children. Postnatal 2, 5-DCP exposure was positively associated with body weight. Sex-specific associations were observed between CPs exposure and childhood growth.